2023
DOI: 10.3934/amc.2021061
|View full text |Cite
|
Sign up to set email alerts
|

Minimal codewords arising from the incidence of points and hyperplanes in projective spaces

Abstract: <p style='text-indent:20px;'>Over the past few years, the codes <inline-formula><tex-math id="M1">\begin{document}$ {\mathcal{C}}_{n-1}(n,q) $\end{document}</tex-math></inline-formula> arising from the incidence of points and hyperplanes in the projective space <inline-formula><tex-math id="M2">\begin{document}$ {\rm{PG}}(n,q) $\end{document}</tex-math></inline-formula> attracted a lot of attention. In particular, small weight codewords of <inline-form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…√ qq n−1 for q = p h with h > 1 in [BD23], building on results by Szőnyi and Weiner [SW18]. The classification was generalised to the codes C k (n, q) in [AD21] for codewords of weight up to roughly 3q k .…”
Section: Results 12 ([Pz18]mentioning
confidence: 99%
“…√ qq n−1 for q = p h with h > 1 in [BD23], building on results by Szőnyi and Weiner [SW18]. The classification was generalised to the codes C k (n, q) in [AD21] for codewords of weight up to roughly 3q k .…”
Section: Results 12 ([Pz18]mentioning
confidence: 99%
“…Finally, the second author and Bartoli [8] showed that if q is not prime and large enough, then codewords of C n−1 (n, q) up to weight roughly 1 2 n−2 q n−1 √ q are linear combinations of exactly wt(c) θ n−1 hyperplanes. One of the aims of this paper is to remove the exponential factor 1 2 n−2 .…”
Section: The General Casementioning
confidence: 99%